Pembuatan Alat Cuci Tangan Otomatis Sebagai Upaya Pencegahan Penularan COVID-19 di Kantor Desa Batukaropa Kecamatan Rilau Ale Kabupaten Bulukumba - Muhammad Awal Nur; Zulfahmi; Ferdiansyah; Nia Uswatul Hasanah; Reski Awaliah (Madani : Indonesian Journal of Civil Society, 2023)
The spread of the Coronavirus infection is expanding consistently. To overcome this, anticipatory and preventative measures are required to stop the spread. Washing your hands is one way to stop the COVID-19 virus from spreading. However, not all public facilities provide hand washing, particularly offices and public service locations that require a portable and adaptable hand washing station. The suggested solution is to create a machine that washes hands automatically and can be moved as needed. This service aims to stop the spread of Covid 19 by providing automatic hand washing equipment at the Batukaropa Village Office. Observation, tool design, tool making, and tool delivery are the methods used. The tool can be used correctly and is beneficial to both the community and the Batukaropa Village Office staff in Rilau Ale District, Bulukumba Regency, South Sulawesi, Indonesia, according to the findings.